2018
DOI: 10.1038/s41366-018-0158-2
|View full text |Cite
|
Sign up to set email alerts
|

Addressing childhood obesity in low-income, ethnically diverse families: outcomes and peer effects of MEND 7–13 when delivered at scale in US communities

Abstract: Implementing MEND 7-13 under service level conditions was associated with short-term improvements in anthropometric, fitness and psychological indices in a large sample of low-income, ethnically diverse children with overweight and obesity. A peer effect was quantified showing that benefits for an individual child were enhanced, if peers in the same group also performed well. To our knowledge, this is the first US study to evaluate outcomes of an up-scaled community-based, child weight management program and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…For example, the translation trial of the Go4Fun face-to-face community-based obesity program for children aged 6-to 14-years in NSW found significant improvements in BMI, however improvements in this outcome were half that of the original RCT. Similarly, a study based on the same program (MEND) conducted in the US found improvements in BMI and cardiovascular fitness, but again much lesser improvements were seen compared to the original RCT [36]. Another community-based child obesity program conducted in Queensland, Australia, found a 5-6% improvement in BMI z-score, but similar to Go4Fun, this was much less than the original RCTs (8-10%) [33].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, the translation trial of the Go4Fun face-to-face community-based obesity program for children aged 6-to 14-years in NSW found significant improvements in BMI, however improvements in this outcome were half that of the original RCT. Similarly, a study based on the same program (MEND) conducted in the US found improvements in BMI and cardiovascular fitness, but again much lesser improvements were seen compared to the original RCT [36]. Another community-based child obesity program conducted in Queensland, Australia, found a 5-6% improvement in BMI z-score, but similar to Go4Fun, this was much less than the original RCTs (8-10%) [33].…”
Section: Discussionmentioning
confidence: 92%
“…The study was partially randomised and had a control group, allowing the opportunity to assess both preference and intervention effects. Unlike some previous translation trials [32,36], an extended follow-up period was included so changes could be assessed long after the completion of the interventions. The study included a range of validated outcome measures which assessed several aspects of dietary intake and movement behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…However, LEFF is the Dutch adaptation of the original MEND intervention, which has been proven to be effective in both randomized and longitudinal examinations. 10,12,13 Therefore, even though the design of the study was not necessarily optimal, the results of this study still provide relevant information. Specifically, the results are in line with the results of MEND, which suggest that this Dutch adaptation of MEND has beneficial effects for children with overweight or obesity.…”
Section: Strengths and Limitationsmentioning
confidence: 96%
“…It has been shown to be effective in reducing weight status and emotional distress, while simultaneously increasing the selfesteem and body esteem of children aged between 7 and 13 years. [10][11][12][13] Given these promising effects, and in light of the absence of any such evidence-based intervention in the Netherlands, the Dutch Ministry of Health financed the project Care for Obesity (C4O) to (among other things) adapt and subsequently pilot this intervention within 11 municipalities, with the express aim of implementing it in cities across the Netherlands. The adapted intervention is called LEFF (Lifestyle, Energy, Fun, and Friends).…”
mentioning
confidence: 99%
“…Unsurprisingly, when obesity prevention interventions are scaled-up, there is generally a reduction in the intervention's effect size on outcomes such as weight status, dietary intake, physical activity and sedentary behaviour, possibly due to lower fidelity to original intervention protocols and increased flexibility in delivery [24]. To date, few childhood interventions to promote healthy eating and appropriate levels of movement behaviours (physical activity, sedentary behaviour and sleep) have been translated and evaluated in real-world settings [25] and most of these translational studies have been conducted in school agedchildren [26][27][28] or infants [29]. Studies using a preference trial design (where at least a proportion of the participants have the option of selecting their preferred study arm), have been conducted successfully in different population groups [30][31][32], but there have been no such studies investigating the effectiveness of a childhood obesity prevention intervention, or any focussing on obesity or obesity-related behaviours in any age group.…”
Section: Introductionmentioning
confidence: 99%